POPULASI SURILI (Presbytis comata) DI BLOK WANAYASA CAGAR ALAM GUNUNG BURANGRANG - Alwi Subhan (Wanamukti: Jurnal Penelitian Kehutanan, 2021)
Gunung Burangrang Natural Reserve is a conservation forest area, and is one of the habitats for Javan Surili, but there is no data on the population of javan Surili. The object of research is to determine how much the population of javan surili in the Wanayasa Block of Gunung Burangrang Nature Reserve. The method of research used the line transect method by data collected of number of individuals, number of groups, sex ratio, and age structure. The research was carried out on four observation lines with varying lengths, observations were made at (05.30 - 11.30 WIB) repetitions were carried out at (13.30 - 18.00 WIB), four repetitions were carried out on each observation path, the results showed that there were 27 surili individuals who were divided into four groups, with the number of groups of 4-9 individuals, and the estimated population density of 1.22 individuals / ha. The sex ratio of male and female surili in the Gunung Burangrang Nature Reserve is 1: 2 where there are more female surile than male surile and for the structure of the largest surile age there are in the adult age class with a percentage of 59.26% then teenagers 29.63%, and the percentage of the smallest amounting to 11.11%